PENGGUNAAN MEDIA KARTU SUKU KATA BERGAMBAR UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS II SDK WOLOMELI - Nenu, Maria Agnes Roswita; Kaka, Pelipus Wungo; Sayangan, Yohanes Vianey; Laksana, Dek Ngurah Laba (STKIP Persada Khatulistiwa Sintang, 2024)
This research was motivated by the low reading ability of class II students at SDK Wolomeli. Learning to read in lower grades is the initial foundation for the development of science. Learning with syllable card media is considered capable of facilitating and strengthening students' memories, increasing insight and skills, attracting students' interest in recognizing several syllables so that students can respond to the meaning of images as a support for students' imagination which provides a connection between the content of learning material and the world. virtual reality through picture imagery, so that students' abilities can develop. This research aims to improve beginning reading skills using illustrated syllable card media for class II students at SDK Wolomeli. The research carried out was classroom action research which cycled through four stages, namely planning, implementation, observation and reflection with the research subjects, namely 13 class II students at SDK Wolomeli, consisting of 5 womens and 8 mens. The results obtained are based on the results of the cycle I and cycle II tests. Students' ability in initial reading has increased. The first cycle of class II students obtained a result of 38% and the second cycle test obtained a result of 71% and there was an increase of 33% so that the level of students' reading ability was included in the quite good category.